Impact of oral diseases on quality of life in subjects attending out-patient department of a dental hospital, India - N Saimadhavi; M. A. K. V. Raju; R Sudhakara Reddy; T Ramesh; D Ayesha Tabassum; K Ramya (Wolters Kluwer Medknow Publications, 2013)
Context: Currently there is a growing interest in oral health outcomes in how oral health affects quality of life. When oral health related quality of life measures are used alongside traditional clinical methods of measuring oral health status, a more comprehensive assessment of the impact of oral diseases on the several dimensions of subjective wellbeing becomes possible. In this context, we attempted to study the impact of oral diseases on quality of life, so as to address the patient's needs in an appropriate way and thereby improving one's quality of life. Aims: To evaluate the impact of different oral diseases on quality of life using a modified OHIP-14 questionnaire, so as to address the patient's needs in an appropriate way and thereby improving one's quality of life. Settings and Design: The study was carried out among 302 subjects, attending the outpatient department a dental hospital, India, for check up and treatment of their oral condition. Subjects aged above 20 years, who gave their consent for the study were included. Materials and Methods: The study sample was categorized in to two groups based upon the duration of the affecting disease - group 1 consisted of subjects suffering with chronic diseases and group 2 of subjects suffering with acute diseases. All the subjects were asked to fill up their responses in the given OHIP-14 questionnaires. The completed questionnaires were then collected and statistically analyzed. Statistical Analysis Used: To evaluate the role of age on QOL, age was divided in to 2 groups using median split procedure. For inter and intragroup comparisions, independent sample t test, anova followed by post hoc test and Chi-square tests were employed. Results: Chi square test revealed a moderately impaired quality of life among all the diseases investigated. On comparing the mean domain and total OHIP score between the two groups, the domain of psychological discomfort and disability and the total OHIP score showed statistically significant values in acute diseases. However, no significant differences were obtained on comparing the grades of QOL in between the two groups. Conclusions: Oral health related quality of life is moderately impaired among those suffering with oral diseases. Routine evaluation using patient centred measures like Oral health Impact Profile during clinical activity is feasible, and provides relevant and useful information for the clinical management of patients with oral mucosa pathology.